A ternary compounded polyester electrolyte composition for aluminum electrolytic capacitor and a preparation method thereof
Patent Information
- Application Number
- CN202611422357.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-14
- Publication Date
- 2026-10-27
AI Technical Summary
该体系有效解决传统电解液功能性组分易迁移分解、高温稳定性差的缺陷,兼顾优异的离子电导率与闪火电压,改善离子液相容性差、耐压性能不足的问题,大幅降低电解液性能衰减速率,适配铝电解电容器耐高温、高耐压、长寿命的严苛使用需求
[0029]本申请提供一种三元复配聚酯型铝电解电容器电解液组合物。本申请首先以直链二元羧酸与多元醇经酯化缩聚构建低支化聚酯中间体,该中间体具有可控的支化点密度与末端活性羟基分布,为后续硼、磷元素的化学锚定提供多位点接枝平台;继而依次与有机膦酸和硼酸反应,分别通过P-O-C和B-O-C共价键将膦酸酯与硼酸酯结构引入聚酯骨架,形成杂化低支化网络。其中膦酸酯基团一方面通过P-O-C键较高的键能提升邻近酯键的热力学稳定性,另一方面其较大的空间位阻对酯键产生屏蔽效应,共同抑制高温下酯交换与醚化副反应,而硼酸酯基团的缺电子硼中心作为Lewis酸位点可配位捕获质子性杂质与游离水分子,两者协同钝化游离质子对铝箔氧化膜的侵蚀通道;与此同时,化学键合的磷/硼元素在电场作用下可定向迁移至阳极氧化膜缺陷位,原位形成P-B复合玻璃态保护层,实现对氧化膜的动态自修复,相较于游离小分子添加剂,该共价锚定方式一定程度上消除了高温服役过程中功能组分的迁移挥发与相分离失效。离子液的引入一方面通过其离域化阳/阴离子对与杂化聚酯骨架的极性酯基及B-O/P-O键发生离子-偶极相互作用,形成连续离子迁移通道,有效提升电解液的本征离子电导率;另一方面离子液与聚酯链段的极性相互作用可降低体系玻璃化转变温度并增加自由体积,从而促进链段运动与离子迁移速率。助剂体系中,硝基芳香羧酸接枝聚乙二醇构成的改性消氢剂,其硝基在阴极极化过程中可被电化学还原为氨基,该还原反应与氢气析出反应形成竞争关系,从而在阴极界面高效捕获并消耗活性氢原子及质子,抑制氢脆与氢气析出,同时聚乙二醇链段的柔顺性保障了消氢活性中心在电解液/氧化膜界面的均匀分散与持续补给;次亚磷酸铵作为氧化膜稳定剂,其电离产生的铵离子可与电解液中微量水分子形成氢键网络,降低游离水活度,同时次亚磷酸根与阳极氧化膜表面铝离子配位形成致密钝化螯合屏障层,有效阻断水分子对氧化膜的水合溶胀侵蚀;聚乙二醇1000或聚乙二醇2000等闪火电压提升剂在高压下通过端羟基与阳极氧化膜表面形成致密氢键吸附层,该吸附层与P-B玻璃态保护层叠加,协同提升氧化膜的介电强度与闪火电压阈值。
Smart Images

Figure CN122991867A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of aluminum electrolytic capacitor technology, specifically to a ternary composite polyester-based aluminum electrolytic capacitor electrolyte composition and its preparation method. Background Technology
[0002] As a core passive electronic component in power supply circuits, digital circuit filters, and various electronic and electrical equipment, the performance of aluminum electrolytic capacitors directly determines the reliability and lifespan of the entire device. The working electrolyte not only determines the capacitor's leakage current, loss tangent, and operating temperature range, but also directly affects its lifespan and withstand voltage characteristics. With the miniaturization, high-frequency operation, and high power density of electronic equipment, the market has placed stringent demands on aluminum electrolytic capacitors, requiring high temperature resistance, long lifespan, high withstand voltage, and low equivalent series resistance (ESR). However, existing working electrolyte systems exhibit significant performance bottlenecks in meeting these requirements.
[0003] Traditional aluminum electrolytic capacitor electrolytes primarily consist of ammonium organic acids and ethylene glycol or branched polycarboxylic acids and their salts. These systems suffer from serious drawbacks under high-temperature conditions: firstly, the solvent and solute are prone to irreversible chemical changes such as hydration and amidation at higher temperatures, leading to deterioration of the electrolyte's chemical composition; secondly, fluctuations in water content can cause unstable leakage current, excessive rate of change, and performance failure during high-temperature storage. To improve the flash voltage and thermal stability of the electrolyte, existing technologies often employ strategies such as adding phosphoric acid or phosphates, boric acid or borate esters. However, these functional components often exist in the electrolyte as free small molecules or physically dispersed forms, making them highly susceptible to migration, volatilization, or decomposition during long-term high-temperature service, resulting in a rapid decline in their interfacial protection and subsequent deterioration of electrolyte performance. Furthermore, while ionic liquids possess high thermal stability and high ionic conductivity and have been attempted for use in aluminum electrolytic capacitor electrolytes in recent years, their flash voltages are generally low, and the compatibility and long-term stability of ionic liquids with existing electrolyte components remain to be addressed. The aforementioned issues collectively restrict the performance of aluminum electrolytic capacitors in high-temperature, high-voltage, and long-life applications.
[0004] In summary, to address the technical challenges of existing aluminum electrolytic capacitor working electrolytes, such as the easy migration and failure of functional components under high-temperature conditions, insufficient chemical stability, and the difficulty in simultaneously achieving high flash voltage and high ionic conductivity, there is an urgent need for a novel electrolyte composition that can stably anchor functional elements such as phosphorus and boron into the electrolyte molecular framework through chemical bonding, while simultaneously possessing both high ionic conductivity and high flash voltage. Summary of the Invention
[0005] To address the aforementioned problems, this application provides a ternary composite polyester electrolyte composition for aluminum electrolytic capacitors and its preparation method. The invention first prepares a low-branched polyester intermediate, then sequentially bonds organophosphonic acid and boric acid to obtain a hybrid polyester substrate. This substrate is then combined with an ionic liquid, a self-made modified hydrogen scavenger, and compounding additives to construct a ternary electrolyte system, chemically anchoring boron and phosphorus functional elements within the molecular framework. This system effectively solves the defects of traditional electrolytes, such as easy migration and decomposition of functional components and poor high-temperature stability. It also achieves excellent ionic conductivity and flash voltage, improves the problems of poor compatibility and insufficient voltage withstand capability of ionic liquids, significantly reduces the electrolyte performance degradation rate, and meets the stringent requirements of aluminum electrolytic capacitors for high temperature resistance, high voltage withstand capability, and long lifespan.
[0006] To achieve the above objectives, one technical solution adopted by the present invention is:
[0007] In a first aspect, the present invention provides a ternary composite polyester-type aluminum electrolytic capacitor electrolyte composition, comprising a borate-phosphonate hybrid low-branched polyester, an ionic liquid, and additives;
[0008] The borate-phosphonate hybrid low-branched polyester is prepared by reacting a low-branched polyester intermediate with an organophosphonic acid and then with borate. The low-branched polyester intermediate is prepared by esterification polycondensation reaction of a straight-chain dicarboxylic acid and a polyol.
[0009] The additives include modified hydrogen scavengers, oxide film stabilizers, and flashover voltage boosters;
[0010] The modified hydrogen scavenger is prepared by esterification grafting reaction of nitroaromatic carboxylic acid and bi-hydroxyl-terminated polyethylene glycol.
[0011] Preferably, the linear dicarboxylic acid includes any one of azelaic acid, sebacic acid, and dodecanoic acid; the polyol includes any one of ethylene glycol, glycerol, and 1,2-propanediol; the organophosphonic acid is methylphosphonic acid; the ionic liquid includes any one of 1-allyl-3-methylimidazolium acetate, 1-ethyl-3-methylimidazolium acetate, and 1-butyl-3-methylimidazolium acetate; the hydroxyl-terminated polyethylene glycol includes any one of polyethylene glycol 200, polyethylene glycol 400, and polyethylene glycol 600; the nitroaromatic carboxylic acid is p-nitrobenzoic acid or m-nitrobenzoic acid; the oxide film stabilizer is ammonium hypophosphite; and the flashover voltage booster is polyethylene glycol 1000 or polyethylene glycol 2000.
[0012] Secondly, the present invention provides a method for preparing a ternary composite polyester-type aluminum electrolytic capacitor electrolyte composition, comprising the following steps:
[0013] S1. Straight-chain dicarboxylic acid and polyol are stirred and mixed evenly, and high-purity nitrogen is introduced to carry out esterification reaction, followed by polycondensation reaction. After the reaction is completed, a low-branched polyester intermediate is obtained.
[0014] S2. Under nitrogen atmosphere and reduced pressure, an organophosphonic acid was added to the low-branched polyester intermediate for the first stirring reaction, followed by the addition of boric acid for the second stirring reaction. After the reaction was completed, the mixture was cooled to room temperature for purification to obtain a borate-phosphonate hybrid low-branched polyester.
[0015] S3. Nitroaromatic carboxylic acid and thionyl chloride were stirred and mixed evenly under a nitrogen atmosphere and then activated to obtain nitrobenzoyl chloride activation intermediate; subsequently, after vacuum distillation, hydroxyl-terminated polyethylene glycol and triethylamine were added and stirred to react. After the reaction was completed, the mixture was naturally cooled to room temperature for purification to obtain modified hydrogen scavenger.
[0016] S4. The borate-phosphonate hybrid low-branched polyester is first stirred and mixed with the ionic liquid; then the modified hydrogen scavenger and oxide film stabilizer are added and stirred and mixed for the second time; finally, the flash voltage booster is added and stirred and mixed for the third time, cooled to room temperature, and filtered to obtain a ternary composite polyester type aluminum electrolytic capacitor electrolyte composition.
[0017] In this application, S1 involves mixing a straight-chain dicarboxylic acid and a polyol under a high-purity nitrogen atmosphere. The nitrogen atmosphere effectively eliminates dissolved oxygen and water vapor in the system, suppressing the oxidation and discoloration of the polyol and the etherification side reaction at high temperatures. During the esterification process, after protonation, the carboxylic acid undergoes a nucleophilic addition-elimination reaction with the hydroxyl group to generate ester bonds and condensed water. The continuous decrease in the acid value of the system indicates the progress of esterification. Subsequently, a polycondensation reaction is carried out under high temperature and high vacuum conditions. The residual carboxyl groups undergo interchain transesterification and dehydration condensation with the hydroxyl or ester groups, gradually constructing a polyester prepolymer with ester bonds as the main chain and abundant active hydroxyl groups at the ends, with a controllable distribution of branching points. These active hydroxyl groups provide a multi-site grafting platform for the subsequent chemical anchoring of boron and phosphorus elements.
[0018] In step S2, under a nitrogen atmosphere, organophosphonic acid is first added to the low-branched polyester intermediate. The phosphonic acid group (-PO(OH)2) reacts with the terminal hydroxyl groups of the polyester in a dehydration esterification reaction, grafting the phosphonate structure onto the branch ends via POC covalent bonds. Immediately after this step, boric acid is added. The B-OH in the boric acid further condenses with the residual hydroxyl groups at a higher temperature, forming BOC bonds to introduce borate ester groups. The organophosphonic acid is added before the boric acid and reacts with the polyester intermediate. The remaining active hydroxyl sites in the system and the polar ester group environment provided by the polyester segments can delay the crystallization and dehydration process by forming a hydrogen bond network with the boric acid, allowing it to participate in esterification grafting in a partially hydrated state or a metaboric acid oligomer state. It can still effectively introduce borate ester groups through BOC bonds. The electron-deficient boron centers of the borate ester groups provide Lewis acid sites for capturing proton impurities. The sequential grafting of both ensures uniform hybridization anchoring and steric hindrance optimization of phosphorus and boron elements on the polyester backbone.
[0019] In step S3, nitroaromatic carboxylic acid and thionyl chloride undergo a nucleophilic acylation reaction under nitrogen protection. The carboxyl group is chlorinated to generate a highly reactive nitrobenzoyl chloride intermediate. Excess thionyl chloride ensures complete conversion of the carboxyl group. Residual thionyl chloride and byproducts sulfur dioxide and hydrogen chloride are removed by vacuum distillation to avoid interference from acidic impurities in subsequent grafting and to prevent hydrolysis of the acyl chloride. Subsequently, bihydroxyl-terminated polyethylene glycol and triethylamine are added. Triethylamine acts as an acid-binding agent to capture the HCl released in the reaction, promoting nucleophilic acylation of the acyl chloride group with the terminal hydroxyl group of polyethylene glycol to form an aromatic ester bond. The nitro aromatic ring is covalently grafted to the end of the polyethylene glycol chain to obtain a modified hydrogen scavenger with an amphiphilic segmental structure. The flexible long chain of polyethylene glycol gives it good dispersion and migration in the electrolyte matrix, while the nitro group is a functional group for electrochemical reduction and capture of active hydrogen.
[0020] In step S4, the borate-phosphonate hybrid low-branched polyester is first mixed with the ionic liquid at a controlled temperature of 50-70°C. The delocalized cation / anion pairs of the ionic liquid interact strongly with the polar ester groups, BO and PO bonds of the hybrid backbone, effectively reducing the physical entanglement between polyester segments and the glass transition temperature of the system, promoting the stretching of polyester molecular chains and the formation of continuous ion migration channels. Subsequently, a modified hydrogen scavenger and an oxide film stabilizer are added and stirred a second time. The polyethylene glycol segments in the modified hydrogen scavenger are coupled with the ionic liquid and polyester backbone through hydrogen bonds and van der Waals forces, promoting the molecular-level dispersion of the nitro active components in the homogeneous system. The ammonium ions and hypophosphite ions generated by the ionization of ammonium hypophosphite are anchored to the polar microregions through hydrogen bonds and coordination, respectively, constructing a chemical water absorption equilibrium buffer system. Finally, a flash voltage booster is added and mixed three times. Polyethylene glycol 1000 or 2000 forms a hydrogen bond network with ester groups and BO / PO bonds in the polar medium through terminal hydroxyl groups. During high-voltage polarization, it preferentially adsorbs and migrates to the anodic oxide film interface to form an insulating adsorption layer. This stepwise gradient mixing strategy effectively avoids the aggregation and precipitation of functional additives due to differences in solubility or competitive interactions, ensuring the coordinated and orderly distribution of each component in the ion conduction network and the interfacial protective layer.
[0021] Preferably, in S1, the stirring speed for uniform mixing is 300-500 r / min; the temperature of the esterification reaction is 160-180℃; the endpoint of the esterification reaction is when the acid value of the system drops to 8-15 mgKOH / g; the vacuum degree of the polycondensation reaction is -0.09 to -0.098 MPa; the temperature of the polycondensation reaction is 190-210℃; and the time of the polycondensation reaction is 2-4 h.
[0022] Preferably, in S1, the mass ratio of the linear dicarboxylic acid to the polyol is 1:(0.45~0.55); and the degree of branching of the low-branched polyester intermediate is 5%~20%.
[0023] Preferably, in S2, the temperature of the first stirring reaction is 110-130°C and the time of the first stirring reaction is 2.5-4 hours; the temperature of the second stirring reaction is 140-160°C and the time of the second stirring reaction is 3-5 hours; and the vacuum degree of the reduced pressure condition is 0.09-0.099 MPa.
[0024] Preferably, in S2, the mass ratio of the low-branched polyester intermediate, organophosphonic acid, and boric acid is 100:(6-15):(3-9).
[0025] Preferably, in S3, the activation reaction temperature is 65-75℃ and the activation reaction time is 5-7h; the vacuum degree of the vacuum distillation is 0.01-0.04MPa, the vacuum distillation temperature is 45-60℃, and the vacuum distillation time is 2-4h; the stirring speed of the stirring reaction is 400-500r / min, the stirring reaction temperature is 60-85℃, and the stirring reaction time is 22-26h; the mass ratio of the nitroaromatic carboxylic acid, sulfonyl chloride, bihydroxyl-terminated polyethylene glycol, and triethylamine is 1:(2.5-4.0):(1.2-3.6):(0.8-1.5).
[0026] Preferably, in S4, the mass ratio of the borate-phosphonate hybrid low-branched polyester, ionic liquid, modified hydrogen scavenger, oxide film stabilizer and flash voltage booster is 100: (20-38): (10-25): (4-10): (7-18).
[0027] Preferably, in S4, the temperature of the first, second, and third mixing is 50–70°C, the mixing speed is 400–600 r / min, the mixing time of the first mixing is 30–60 min, the mixing time of the second mixing is 40–80 min, and the mixing time of the third mixing is 1.5–3 h.
[0028] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0029] This application provides a ternary composite polyester electrolyte composition for aluminum electrolytic capacitors. First, a low-branched polyester intermediate is constructed by esterification and polycondensation of a linear dicarboxylic acid and a polyol. This intermediate has a controllable branching point density and terminal active hydroxyl distribution, providing a multi-site grafting platform for subsequent chemical anchoring of boron and phosphorus elements. Then, it reacts sequentially with organophosphonic acid and boric acid, respectively, introducing phosphonate and borate ester structures into the polyester backbone through POC and BOC covalent bonds, forming a hybrid low-branched network. Phosphonate groups enhance the thermodynamic stability of adjacent ester bonds through the high bond energy of POC bonds, while their large steric hindrance shields the ester bonds, jointly suppressing transesterification and etherification side reactions at high temperatures. Meanwhile, the electron-deficient boron centers of borate ester groups, acting as Lewis acid sites, can coordinate and capture protonated impurities and free water molecules. Together, they passivate the erosion channels of free protons on the aluminum foil oxide film. At the same time, chemically bonded phosphorus / boron elements can migrate directionally to the defect sites of the anodic oxide film under the action of an electric field, forming a PB composite glassy protective layer in situ, achieving dynamic self-repair of the oxide film. Compared with free small molecule additives, this covalent anchoring method eliminates the migration, volatilization, and phase separation failure of functional components during high-temperature service to a certain extent. The introduction of ionic liquids enhances the intrinsic ionic conductivity of the electrolyte by creating continuous ion migration channels through ion-dipole interactions between the delocalized cation / anion pairs and the polar ester groups and BO / PO bonds of the hybrid polyester backbone. Furthermore, the polar interaction between the ionic liquid and polyester segments lowers the glass transition temperature and increases free volume, thereby promoting segment movement and ion migration rates. In the additive system, the modified hydrogen scavenger composed of nitroaromatic carboxylic acid grafted with polyethylene glycol exhibits electrochemical reduction of its nitro groups to amino groups during cathode polarization. This reduction reaction competes with the hydrogen evolution reaction, efficiently capturing and consuming active hydrogen atoms and protons at the cathode interface, inhibiting hydrogen embrittlement and hydrogen evolution. Simultaneously, the flexibility of the polyethylene glycol segments ensures uniform dispersion and continuous replenishment of the hydrogen scavenging active centers at the electrolyte / oxide film interface. Ammonium hypophosphite, acting as an oxide film stabilizer, generates ammonium ions upon ionization. The ions can form a hydrogen bond network with trace water molecules in the electrolyte, reducing the activity of free water. At the same time, hypophosphite ions coordinate with aluminum ions on the surface of the anodic oxide film to form a dense passivation chelate barrier layer, effectively blocking the hydration and swelling erosion of the oxide film by water molecules. Under high voltage, flash voltage enhancers such as polyethylene glycol 1000 or polyethylene glycol 2000 form a dense hydrogen bond adsorption layer on the surface of the anodic oxide film through terminal hydroxyl groups. This adsorption layer is superimposed with the PB glassy protective layer, synergistically improving the dielectric strength and flash voltage threshold of the oxide film.
[0030] The above components are mixed in a stepwise gradient. First, a homogeneous ion-conducting matrix is established by premixing hybrid polyester and ionic liquid. Then, hydrogen scavengers and oxide film stabilizers are introduced to regulate the interfacial chemical microenvironment. Finally, a flash voltage booster is added to optimize high-voltage tolerance. The components form a close synergy in three dimensions: chemical bonding, ion conduction and interfacial protection. This ensures high ionic conductivity while simultaneously improving flash voltage and high-temperature long-life performance. Attached Figure Description
[0031] Figure 1 This is a physical image of a ternary composite polyester-type aluminum electrolytic capacitor electrolyte composition according to Example 3. Detailed Implementation
[0032] The technical solutions in the embodiments of this application will be clearly and completely described below with reference to the embodiments of this application. Obviously, the embodiments described below are only some embodiments of this application, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.
[0033] The terminology used in this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application.
[0034] The terms “for,” “or,” “a,” “any,” and “described” as used in this application are intended to include the majority form unless the context clearly indicates otherwise.
[0035] Furthermore, the terms "first" and "second" appearing in this application are for descriptive purposes only and should not be construed as indicating or implying relative importance.
[0036] The specific embodiments of this application will be further described in detail below with reference to the accompanying drawings, in conjunction with specific examples and comparative examples.
[0037] Example 1
[0038] This embodiment provides a method for preparing a ternary composite polyester-based aluminum electrolytic capacitor electrolyte composition, comprising the following steps:
[0039] S1. Azelaic acid and ethylene glycol are stirred and mixed evenly at 300 r / min, and esterified at 160℃ under high-purity nitrogen gas until the acid value of the system drops to 8 mg KOH / g. Then, polycondensation reaction is carried out at 190℃ under vacuum of -0.09 MPa for 4 h. After the reaction is completed, a low-branched polyester intermediate with a branching degree of 5% is obtained; the mass ratio of azelaic acid to ethylene glycol is 1:0.45.
[0040] S2. Methylphosphonic acid was added to the low-branched polyester intermediate under a nitrogen atmosphere and a vacuum of 0.09 MPa. The mixture was stirred at 110°C for 4 hours, followed by the addition of boric acid at 140°C for 5 hours. After the reaction was completed, the mixture was cooled to room temperature and purified to obtain a borate-phosphonate hybrid low-branched polyester. The mass ratio of the low-branched polyester intermediate, methylphosphonic acid, and boric acid was 100:6:3.
[0041] S3. p-Nitrobenzoic acid and sulfoxide were stirred and mixed uniformly at 300 r / min under a nitrogen atmosphere, and activated at 65 °C for 7 h to obtain nitrobenzyl chloride activated intermediate; then, polyethylene glycol 200 and triethylamine were added after vacuum distillation at 45 °C for 4 h under a vacuum of 0.01 MPa, and the mixture was stirred at 60 °C for 26 h under a nitrogen atmosphere at 400 r / min. After the reaction was completed, the mixture was naturally cooled to room temperature for purification to obtain modified hydrogen scavenger; the mass ratio of p-nitrobenzoic acid, sulfoxide, polyethylene glycol 200 and triethylamine was 1:2.5:1.2:0.8;
[0042] S4. First, the borate-phosphonate hybrid low-branched polyester is mixed with 1-allyl-3-methylimidazolium acetate and stirred for 60 minutes at 50°C and 400 r / min. Then, a modified hydrogen scavenger and ammonium hypophosphite are added and stirred for 80 minutes. Finally, polyethylene glycol 1000 is added and stirred for 3 hours. The mixture is then cooled to room temperature and filtered to obtain a ternary composite polyester-type aluminum electrolytic capacitor electrolyte composition. The mass ratio of the borate-phosphonate hybrid low-branched polyester, 1-allyl-3-methylimidazolium acetate, modified hydrogen scavenger, ammonium hypophosphite, and polyethylene glycol 1000 is 100:20:10:4:7.
[0043] Example 2
[0044] This embodiment provides a method for preparing a ternary composite polyester-based aluminum electrolytic capacitor electrolyte composition, comprising the following steps:
[0045] S1. Sebacic acid and glycerol were stirred and mixed evenly at 400 r / min, and esterified at 170℃ under high-purity nitrogen until the acid value of the system dropped to 12 mg KOH / g. Then, polycondensation was carried out at 200℃ under a vacuum of -0.094 MPa for 3 h. After the reaction was completed, a low-branched polyester intermediate with a branching degree of 14% was obtained; the mass ratio of sebacic acid to glycerol was 1:0.5.
[0046] S2. Methylphosphonic acid was added to the low-branched polyester intermediate under a nitrogen atmosphere and a vacuum degree of 0.094 MPa. The mixture was stirred at 120°C for 3 hours, followed by the addition of boric acid at 150°C for 4 hours. After the reaction was completed, the mixture was cooled to room temperature and purified to obtain a borate-phosphonate hybrid low-branched polyester. The mass ratio of the low-branched polyester intermediate, methylphosphonic acid, and boric acid was 100:10:6.
[0047] S3. m-Nitrobenzoic acid and sulfoxide were stirred and mixed uniformly at 350 r / min under a nitrogen atmosphere, and activated at 70 °C for 6 h to obtain an activated intermediate of nitrobenzyl chloride. Subsequently, polyethylene glycol 400 and triethylamine were added after vacuum distillation at 50 °C for 3 h under a vacuum of 0.03 MPa. The mixture was stirred and reacted at 75 °C for 24 h under a nitrogen atmosphere at 450 r / min. After the reaction was completed, the mixture was naturally cooled to room temperature for purification to obtain a modified hydrogen scavenger. The mass ratio of m-nitrobenzoic acid, sulfoxide, polyethylene glycol 400, and triethylamine was 1:3:2.4:1.1.
[0048] S4. First, the borate-phosphonate hybrid low-branched polyester is mixed with 1-ethyl-3-methylimidazolium acetate and stirred for 45 minutes at 60°C and 500 r / min. Then, a modified hydrogen scavenger and an oxide film stabilizer are added and stirred for 60 minutes. Finally, polyethylene glycol 2000 is added and stirred for 2 hours. After cooling to room temperature, the mixture is filtered to obtain a ternary composite polyester-type aluminum electrolytic capacitor electrolyte composition. The mass ratio of the borate-phosphonate hybrid low-branched polyester, 1-ethyl-3-methylimidazolium acetate, modified hydrogen scavenger, ammonium hypophosphite, and polyethylene glycol 2000 is 100:29:18:7:13.
[0049] Example 3
[0050] A method for preparing a ternary composite polyester-based aluminum electrolytic capacitor electrolyte composition includes the following steps:
[0051] S1. Dodecanoic acid and 1,2-propanediol are stirred and mixed evenly at 500 r / min. High-purity nitrogen is introduced and esterification reaction is carried out at 180℃ until the acid value of the system drops to 15 mg KOH / g. Subsequently, polycondensation reaction is carried out at 210℃ under vacuum of -0.098 MPa for 2 h. After the reaction is completed, a low-branched polyester intermediate with a branching degree of 20% is obtained. The mass ratio of dodecanoic acid to 1,2-propanediol is 1:0.55.
[0052] S2. Methylphosphonic acid was added to the low-branched polyester intermediate under a nitrogen atmosphere and a vacuum degree of 0.099 MPa. The mixture was stirred for the first time at 130°C for 2.5 h, followed by the addition of boric acid and the second stirring for 3 h at 160°C. After the reaction was completed, the mixture was cooled to room temperature and purified to obtain a borate-phosphonate hybrid low-branched polyester. The mass ratio of the low-branched polyester intermediate, methylphosphonic acid, and boric acid was 100:15:9.
[0053] S3. p-Nitrobenzoic acid and sulfoxide were stirred and mixed uniformly at 400 r / min under a nitrogen atmosphere, and activated at 75 °C for 5 h to obtain nitrobenzyl chloride activated intermediate; then, polyethylene glycol 600 and triethylamine were added after vacuum distillation at 60 °C for 2 h under a vacuum of 0.04 MPa, and stirred at 85 °C for 22 h under a nitrogen atmosphere. After the reaction was completed, the mixture was naturally cooled to room temperature for purification to obtain modified hydrogen scavenger; the mass ratio of p-nitrobenzoic acid, sulfoxide, polyethylene glycol 600 and triethylamine was 1:4.0:3.6:1.5;
[0054] S4. The borate-phosphonate hybrid low-branched polyester is mixed with 1-butyl-3-methylimidazolium acetate. The mixture is first stirred and mixed for 30 minutes at 70°C and 600 r / min. Then, a modified hydrogen scavenger and ammonium hypophosphite are added, and the mixture is stirred and mixed for a second time for 40 minutes. Finally, polyethylene glycol 2000 is added, and the mixture is stirred and mixed for a third time for 1.5 hours. The mixture is then cooled to room temperature and filtered to obtain a ternary composite polyester-based aluminum electrolytic capacitor electrolyte composition. Figure 1 The mass ratio of the borate-phosphonate hybrid low-branched polyester, 1-butyl-3-methylimidazolium acetate, modified hydrogen scavenger, ammonium hypophosphite, and polyethylene glycol 2000 is 100:38:25:10:18.
[0055] Comparative Example 1
[0056] A method for preparing a ternary composite polyester-based aluminum electrolytic capacitor electrolyte composition differs from Example 3 in that, in step S2, no organic phosphonic acid and boric acid are added for chemical bonding modification. Instead, the unhybridized pure low-branched polyester intermediate is directly used to replace the borate-phosphonate hybrid low-branched polyester for all subsequent steps, thus eliminating the phosphorus-boron bonding modification step. Other process parameters and operating conditions are exactly the same as in Example 3.
[0057] Comparative Example 2
[0058] A method for preparing a ternary composite polyester-type aluminum electrolytic capacitor electrolyte composition differs from Example 3 in that the modified hydrogen scavenger prepared in S3 is omitted, and conventional ungrafted polyethylene glycol nitroaromatic carboxylic acid is used as an equal substitute. Other process parameters and operating conditions are exactly the same as in Example 3.
[0059] Comparative Example 3
[0060] A method for preparing a ternary composite polyester-type aluminum electrolytic capacitor electrolyte composition, which differs from Example 3 in that no ionic liquid is added in step S4, while other process parameters and operating conditions are exactly the same as in Example 3.
[0061] Performance testing:
[0062] 1. High-temperature accelerated load life test: The ternary composite polyester type aluminum electrolytic capacitor electrolyte compositions prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were injected into aluminum electrolytic capacitors with a rated voltage of 450V. The rated ripple current was applied at an ambient temperature of 125℃ for high-temperature load test. Every 300 hours, the capacitor was taken out and the capacitance change rate (ΔC / C), loss tangent (tanδ) and leakage current (LC) were measured. The test was continued until 3000 hours. The capacitance change rate, tanδ value and leakage current value of each example and comparative example at 3000h were recorded.
[0063] 2. Flash voltage and ionic conductivity tests: The ternary composite polyester-type aluminum electrolytic capacitor electrolyte compositions prepared in Examples 1-3 and Comparative Examples 1-3 were placed in a constant temperature bath with four temperature gradients: 30℃, 85℃, 105℃, and 125℃. The ionic conductivity (σ, mS / cm) at each temperature was measured using a conductivity meter. At the same time, an equal amount of electrolyte was placed in a flash voltage test device, with a platinum sheet as the cathode and an aluminum sheet as the anode. A DC voltage was applied at a voltage rise rate of 10V / s, and the maximum voltage value when a continuous spark discharge appeared on the anode surface was recorded as the flash voltage (V). The ionic conductivity values of each example and comparative example at the four temperature gradients and the flash voltage value at 30℃ were recorded.
[0064] 3. Stability Test: The ternary composite polyester-type aluminum electrolytic capacitor electrolyte compositions prepared in Examples 1-3 and Comparative Examples 1-3 were sealed and stored in a constant temperature oven at 150℃ for 500 hours. The pH value and water content of the electrolyte were measured before and after storage (Karl Fischer method). The change in pH value (ΔpH) and the increase in water content (ΔH2O, ppm) were calculated. Simultaneously, the ionic conductivity at 25℃ before and after storage was measured, and the rate of change in conductivity Δσ = (σ... 后 -σ 前 )×100% / σ 前 , where σ 前 σ represents the initial ionic conductivity at 25°C before high-temperature storage. 后 The values are the ionic conductivity measured at 25°C after 500 hours of high-temperature storage. The ΔpH, ΔH2O, and Δσ of each example and comparative example after 500 hours of high-temperature storage were recorded.
[0065] Table 1. Load life test data of the electrolyte compositions for ternary composite polyester aluminum electrolytic capacitors in Examples 1-3 and Comparative Examples 1-3.
[0066] Example 1 -8.2 0.092 125 Example 2 -5.6 0.085 86 Example 3 -5.2 0.078 65 Comparative Example 1 -18.5 0.220 380 Comparative Example 2 -12.3 0.190 210 Comparative Example 3 -9.7 0.170 145
[0067] Table 2. Flash voltage and ionic conductivity test data of the ternary composite polyester aluminum electrolytic capacitor electrolyte compositions of Examples 1-3 and Comparative Examples 1-3
[0068]
[0069] Table 3. Stability test data of the ternary composite polyester aluminum electrolytic capacitor electrolyte compositions of Examples 1-3 and Comparative Examples 1-3
[0070] Example 1 -0.25 140 4.8 Example 2 -0.22 120 4.5 Example 3 -0.15 75 2.8 Comparative Example 1 -0.85 420 18.5 Comparative Example 2 -0.55 350 10.2 Comparative Example 3 -0.28 160 5.5
[0071] As can be seen from the data in Tables 1 to 3, Examples 1 to 3 achieve improvements in high-temperature load life, flash voltage and ionic conductivity, and high-temperature storage chemical stability of the electrolyte through the synergistic effect of the three components: borate-phosphonate covalent anchoring framework, ionic liquid ion conduction channel, and auxiliary agent system interface protection. Among them, Example 3 has the best matching degree of the entire set of process parameters, and many key indicators are at the best level among all groups. Figure 1It can be seen that the electrolyte composition of the ternary composite polyester aluminum electrolytic capacitor is an orange-yellow transparent viscous liquid, with a homogeneous system, free of suspended matter and stratification. Corresponding to the data in Table 1, Example 3, under the harsh operating conditions of 125℃×3000h, showed a capacitance change rate of only -5.2%, a tanδ as low as 0.078, and a leakage current of only 65μA. This indicates that the covalent bonds of POC and BOC in the hybrid polyester skeleton stably anchor phosphorus and boron elements to the molecular chain, preventing migration, volatilization, and phase separation during long-term high-temperature service. The PB composite glassy protective layer continuously repairs defects in the anodic oxide film, effectively suppressing leakage current increases and dielectric degradation at high temperatures. Corresponding to the data in Table 2, Example 3 showed a flashover voltage of 525V at room temperature and 492V at 125℃. Simultaneously, the ionic conductivity reached 2.5mS / cm at 30℃ and as high as 15.0mS / cm at 125℃, indicating strong ionic coupling between the ionic liquid and the hybrid polyester skeleton. The interaction between the electrodes creates a highly efficient ion migration channel. At the same time, the insulating polymer layer formed on the oxide film surface by the flash voltage booster and the PB glassy protective layer are superimposed, achieving a simultaneous balance between high ionic conductivity and high flash voltage. According to the data in Table 3, after 500 hours of high-temperature storage in Example 3, the ΔpH was only -0.15, the ΔH2O was only 75ppm, and the conductivity change rate was only 2.8%, indicating that the chemically bonded phosphorus / boron elements fundamentally eliminated the migration and decomposition of functional components. The PEG flexible segments in the modified hydrogen scavenger ensured the uniform dispersion and continuous hydrogen scavenging of the nitro active centers at the interface. The ammonium hypophosphite oxide film stabilizer effectively reduced the free water activity and coordinating and passivated the oxide film surface. The three synergistically maintained the chemical composition stability of the electrolyte under high-temperature conditions.
[0072] Compared to Example 3, Comparative Example 1 omits the chemical bonding process of S2 organophosphonic acid and boric acid, completely lacking phosphorus and boron functional elements. The polyester skeleton is used directly in the form of unhybridized pure low-branched polyester. Lacking the chemical anchoring of POC and BOC covalent bonds, the polyester skeleton loses the in-situ self-healing ability of the PB composite glassy protective layer. During long-term high-temperature service, the defect sites of the anodic oxide film are continuously exposed and eroded. In Table 1, the leakage current soars to 380 μA, tanδ reaches 0.220, and the capacitance change rate reaches -18.5%. In Table 2, the flashover voltage at room temperature drops to 495 V, and the flashover voltage at 125°C drops to 440 V. Simultaneously, the ionic conductivity decreases across all temperature gradients, reaching only 1.4 at 30°C. The concentration of phosphorus / boron (mS / cm) at 125℃ is only 6.8 mS / cm, indicating that the lack of phosphorus / boron covalent anchoring results in insufficient polar sites in the polyester skeleton, preventing the ionic liquid from forming continuous migration channels through ion-dipole interactions. Table 3 shows that ΔpH reaches -0.85, ΔH2O is as high as 420 ppm, and the conductivity change rate is 18.5%, which are 5.7 times, 5.6 times, and 6.6 times that of Example 3, respectively. This indicates that pure polyester undergoes significant hydration reactions and ester bond hydrolysis at high temperatures, leading to severe chemical instability. These three data tables collectively confirm that the covalent bonding of POC and BOC is the core foundation for achieving high-temperature stable anchoring of functional components, dynamic repair of the oxide film, and chemical stability of the electrolyte.
[0073] Compared to Example 3, Comparative Example 2 omitted the S3 acylation-esterification grafting reaction and used an equal amount of ungrafted polyethylene glycol p-nitrobenzoic acid to replace the modified hydrogen scavenger. Unmodified nitrobenzoic acid lacks the molecular-level dispersion ability of the flexible polyethylene glycol segments, and the nitro active centers locally aggregate in the electrolyte matrix, failing to achieve uniform coverage and continuous hydrogen scavenging replenishment at the electrolyte / oxide film interface. Table 1 shows that the leakage current increased to 210 μA, tanδ reached 0.17, and the capacitance change rate was -12.3%, indicating that local hydrogen evolution was not effectively suppressed, and the accumulation of hydrogen pressure led to mechanical damage and interface degradation of the oxide film. Table 2 shows that the flashover voltage at room temperature was 505 V, the flashover voltage at 125℃ was 455 V, the ionic conductivity at 30℃ was 1.6 mS / cm, and the ionic conductivity at 125℃ was 9.0 mS / cm. Although it was better than Comparative Example 1 due to P / B covalent bonding and ionic liquid retention, the ionic conductivity and flashover voltage at each temperature were lower than those of Example 3. Table 3 shows that ΔH2O was as high as 350 ppm, which was 3.7 times higher than 75 ppm in Example 3. This indicates that the lack of hydrogen bond network association between PEG segments and water molecules significantly reduced the water absorption buffering efficiency of the oxide film stabilizer, and the increased free water activity caused hydration swelling and erosion. The data in Tables 1 and 3 together confirm that PEG grafting endows the hydrogen scavenger with molecular-level dispersibility and continuous interfacial replenishment capability, which is the key design for inhibiting hydrogen evolution and synergistically preventing water recombination.
[0074] Compared to Example 3, Comparative Example 3 omitted the ionic liquid in S4, retaining only the binary system of hybrid polyester and additives. Without the delocalized cation / anion pairs of the ionic liquid and the ion-dipole interaction between the polar ester groups of the hybrid polyester, the electrolyte lost its intrinsic ability to construct continuous ion migration channels. Table 2 shows a sharp drop in ionic conductivity across all temperatures, only 1.1 mS / cm at 30℃ and only 6 mS / cm at 125℃, representing 44% and 40% of Example 3, respectively. The increased equivalent series impedance exacerbated dielectric loss under high-temperature ripple current. Notably, Comparative Example 3 had a flashover voltage of 510V at room temperature and 465V at 125℃. Although slightly lower than Example 3's 525V / 492V due to the absence of the ionic liquid, it was still significantly higher than Comparative Example 1 (495V / 440V) and Comparative Example 2 (505V / 455V), indicating that the flashover voltage is mainly determined by the PB covalent bonding layer and the flashover voltage enhancer. The data comparison strongly demonstrates that this application solves the technical bottleneck of the difficulty in simultaneously achieving high flash voltage and high ionic conductivity by decoupling and compounding the ionic liquid (responsible for ionic conductivity) with the P / B covalent anchoring and flash voltage enhancer functions. In Table 3, Δσ is 5.5% and ΔH2O is 160 ppm, indicating that chemical stability can be maintained due to the retention of the P / B covalent bond and auxiliary agent system. However, the conductivity change rate is still higher than the 2.8% in Example 3, indicating that the polar interaction between the ionic liquid and the polyester skeleton has an irreplaceable stabilizing contribution to the regulation of the system's free volume and chain segment movement at high temperatures. The three data tables jointly confirm that the ionic liquid is the core component for constructing a high ionic conductivity matrix, and its synergistic compounding with the hybrid polyester achieves a decoupling and simultaneous achievement of high conductivity and high flash voltage.
[0075] In summary, the ternary composite systems in Examples 1-3 achieve complementary synergy through three dimensions: POC / BOC covalent bonding anchoring, ionic liquid ion-dipole conduction, and auxiliary agent interface protection and regulation. This solves the technical problems of existing aluminum electrolytic capacitor working electrolytes, such as easy migration and failure of functional components under high-temperature conditions, insufficient chemical stability, and the difficulty in simultaneously achieving flash voltage and ionic conductivity. Example 3, with its optimal process parameter matching, achieves optimal high-temperature load life, flash voltage, ionic conductivity, and high-temperature storage stability. The resulting ternary composite polyester-type aluminum electrolytic capacitor electrolyte composition can stably meet the stringent service requirements of aluminum electrolytic capacitors in high-temperature, high-voltage, and long-life application scenarios.
[0076] The above description is merely a preferred embodiment of the present invention. The scope of protection of the present invention is not limited to the above embodiments. All technical solutions falling within the scope of the present invention's concept are within the scope of protection of the present invention. It should be noted that for those skilled in the art, any improvements and modifications made without departing from the principles of the present invention should also be considered within the scope of protection of the present invention.
Claims
1. A ternary composite polyester-based aluminum electrolytic capacitor electrolyte composition, characterized in that, Includes borate-phosphonate hybrid low-branched polyesters, ionic liquids, and auxiliaries; The borate-phosphonate hybrid low-branched polyester is prepared by reacting a low-branched polyester intermediate with an organophosphonic acid and then with borate. The low-branched polyester intermediate is prepared by esterification polycondensation reaction of a straight-chain dicarboxylic acid and a polyol. The additives include modified hydrogen scavengers, oxide film stabilizers, and flashover voltage boosters; The modified hydrogen scavenger is prepared by esterification grafting reaction of nitroaromatic carboxylic acid and bi-hydroxyl-terminated polyethylene glycol.
2. The ternary composite polyester-type aluminum electrolytic capacitor electrolyte composition according to claim 1, characterized in that, The linear dicarboxylic acid includes any one of azelaic acid, sebacic acid, and dodecanoic acid; the polyol includes any one of ethylene glycol, glycerol, and 1,2-propanediol; the organophosphonic acid is methylphosphonic acid; the ionic liquid includes any one of 1-allyl-3-methylimidazolium acetate, 1-ethyl-3-methylimidazolium acetate, and 1-butyl-3-methylimidazolium acetate; the hydroxyl-terminated polyethylene glycol includes any one of polyethylene glycol 200, polyethylene glycol 400, and polyethylene glycol 600; the nitroaromatic carboxylic acid is p-nitrobenzoic acid or m-nitrobenzoic acid; the oxide film stabilizer is ammonium hypophosphite; and the flashover voltage booster is polyethylene glycol 1000 or polyethylene glycol 2000.
3. A method for preparing the electrolyte composition of a ternary composite polyester-type aluminum electrolytic capacitor as described in any one of claims 1-2, characterized in that, Includes the following steps: S1. Straight-chain dicarboxylic acid and polyol are stirred and mixed evenly, and high-purity nitrogen is introduced to carry out esterification reaction, followed by polycondensation reaction. After the reaction is completed, a low-branched polyester intermediate is obtained. S2. Under nitrogen atmosphere and reduced pressure, an organophosphonic acid was added to the low-branched polyester intermediate for the first stirring reaction, followed by the addition of boric acid for the second stirring reaction. After the reaction was completed, the mixture was cooled to room temperature for purification to obtain a borate-phosphonate hybrid low-branched polyester. S3. Nitroaromatic carboxylic acid and thionyl chloride were stirred and mixed evenly under a nitrogen atmosphere and then activated to obtain nitrobenzoyl chloride activation intermediate; subsequently, after vacuum distillation, hydroxyl-terminated polyethylene glycol and triethylamine were added and stirred to react. After the reaction was completed, the mixture was naturally cooled to room temperature for purification to obtain modified hydrogen scavenger. S4. The borate-phosphonate hybrid low-branched polyester is first stirred and mixed with the ionic liquid; then the modified hydrogen scavenger and oxide film stabilizer are added and stirred and mixed for the second time; finally, the flash voltage booster is added and stirred and mixed for the third time, cooled to room temperature, and filtered to obtain a ternary composite polyester type aluminum electrolytic capacitor electrolyte composition.
4. The method for preparing a ternary composite polyester-type aluminum electrolytic capacitor electrolyte composition according to claim 3, characterized in that, In S1, the stirring speed for uniform mixing is 300-500 r / min; the temperature of the esterification reaction is 160-180℃; the endpoint of the esterification reaction is when the acid value of the system drops to 8-15 mgKOH / g; the vacuum degree of the polycondensation reaction is -0.09 to -0.098 MPa; the temperature of the polycondensation reaction is 190-210℃; and the time of the polycondensation reaction is 2-4 h.
5. The method for preparing a ternary composite polyester-type aluminum electrolytic capacitor electrolyte composition according to claim 3, characterized in that, In S1, the mass ratio of the straight-chain dicarboxylic acid to the polyol is 1:(0.45~0.55).
6. The method for preparing a ternary composite polyester-type aluminum electrolytic capacitor electrolyte composition according to claim 3, characterized in that, In S2, the temperature of the first stirring reaction is 110-130℃ and the time of the first stirring reaction is 2.5-4h; the temperature of the second stirring reaction is 140-160℃ and the time of the second stirring reaction is 3-5h; the vacuum degree of the reduced pressure condition is 0.09-0.099MPa.
7. The method for preparing a ternary composite polyester-type aluminum electrolytic capacitor electrolyte composition according to claim 3, characterized in that, In S2, the mass ratio of the low-branched polyester intermediate, organophosphonic acid, and boric acid is 100:(6-15):(3-9).
8. The method for preparing a ternary composite polyester-type aluminum electrolytic capacitor electrolyte composition according to claim 3, characterized in that, In S3, the activation reaction temperature is 65-75℃ and the activation reaction time is 5-7h; the vacuum degree of the vacuum distillation is 0.01-0.04MPa, the vacuum distillation temperature is 45-60℃, and the vacuum distillation time is 2-4h; the stirring speed of the stirring reaction is 400-500r / min, the stirring reaction temperature is 60-85℃, and the stirring reaction time is 22-26h; the mass ratio of the nitroaromatic carboxylic acid, sulfonyl chloride, bihydroxyl-terminated polyethylene glycol, and triethylamine is 1:(2.5-4.0):(1.2-3.6):(0.8-1.5).
9. The method for preparing a ternary composite polyester-type aluminum electrolytic capacitor electrolyte composition according to claim 3, characterized in that, In S4, the mass ratio of the borate-phosphonate hybrid low-branched polyester, ionic liquid, modified hydrogen scavenger, oxide film stabilizer and flash voltage booster is 100: (20-38): (10-25): (4-10): (7-18).
10. The method for preparing a ternary composite polyester-type aluminum electrolytic capacitor electrolyte composition according to claim 3, characterized in that, In S4, the temperature for the first, second, and third mixing is 50–70°C, the mixing speed is 400–600 r / min, the mixing time for the first mixing is 30–60 min, the mixing time for the second mixing is 40–80 min, and the mixing time for the third mixing is 1.5–3 h.